Improving Science Learning Outcomes in Water Clearance Material with Science, Technology, Engineering, and Mathematics (Stem) Approaches - Marti Marni; Jahdiah Jahdiah (JSEP (Journal of Science Education and Practice), 2022)
This study aims to improve the Learning Outcomes of Science, Technology, Engineering, and Mathematics (STEM) Water Purification Materials for Class IX Junior High School Students. This research is a Classroom Action Research (CAR). The Research Procedure includes two cycles. The instruments used for the assessment of learning outcomes are teacher and student observation sheets. From the analysis of the assessment of student learning outcomes, there is an increase in learning outcomes after using the Science, Technology, Engineering, and Mathematics (STEM) approach to Water Purification material, namely from 21 students there are 4 (19.05%) students have high learning outcomes in the cycle category. 1 while in cycle 2 there were 18 (85.71%) students. From the analysis of teacher observations in cycle 1 of the medium category and cycle 2 of the high category. Meanwhile, from the analysis of student activities in cycle 1 for aspects of interest, attention, participation, and presentation in the moderate category and cycle 2 in all these aspects in the high category Based on the research, it can concluded that there is an increase in science learning outcomes in water purification material with the Science, Technology, Engineering and Mathematical, (STEM) approach in class IX students of SMP.